Satisfaction in Prosthesis Denture campaign for the elderly to celebrate 80th Anniversary His Majesty's the King In Roi-Et Province under Universal Coverage Project Year 2006. - ทีฆายุพันธุ์, สุชาดา; พาดี, พีรวิชญ์ (Thai Dental Public Health Journal, 2008)
The objective of this study was to find knowing satisfaction assessment of artificial teeth replacement service of the Royal project and satisfaction comparison of aging population group receiving this service for the first time to the other group receiving this service more than one time. These groups were in the area of 17 district of Roi-et province. Number of the studies examples were 158 by the systemic random selection. Tools used for data collection were satisfaction assessment form. Statistics used for data analysis were frequency, mean, percentage, standard deviation and independent sample t-test method for difference comparison. Result of studies had shown that 91.1 percent of aging population group received artificial teeth replacement service from Government health Service Unit, 69.6 percent received this service for the first time, 72.2 percent replaced all teeth with artificial teeth, 99.4 percent were advised how to take care of their teeth and artificial teeth from dental officers. After this group received artificial teeth replacement they found that 96.2 percent could use their artificial teeth as normal, 89.9 percent used their artificial teeth for food chewing and making them to be good looking. The feeling after receiving this service were 91.1 percent of them could chew and eat more food, 77.8 percent were good emotion and felt free to smile, 77.5 percent were more good looking, 70.9 percent were happy. In conclusion, 79.7 percent of them were high satisfied. Comparision of satisfaction mean score value of the group receiving this service for the first time to the other group, there were no difference between them (p >0.05). This study had shown that 79.7 percent of the group receiving this service were high satisfied which reflected good service quality and advice. All data from this study should be used for service quality improvement and development of dental personnel.